The sloth life : dream on! - Emerson, Joan; May, Kyla (New York : Scholastic Inc, 2020)
Meet Sloth! He believes that relaxing is an art form, that slippers are an underrated fashion accessory, and that there's nothing better than a nap except for two naps. Or five.
K-3
3.3
Keywords: Sloths -- Juvenile fiction; Sloths -- Fiction; Naps (Sleep) -- Juvenile fiction; Naps (Sleep) -- Fiction; Humorous stories; Animals